Sintesis dan Karakterisasi Silika Sekam Padi sebagai Material Self-Cleaning - Elsandika, Gabriela; Dirgantara, Made; Beladona, Siti Unvaresi Misonia; Pasaribu, Marvin Horale (Jurnal Fisika Unand, 2025)
This study aimed to valorize rice husk waste by extracting silica and developing a self-cleaning surface coating. Silica was successfully extracted from rice husk ash via an alkaline reflux method followed by acid precipitation. The extracted silica exhibited an amorphous structure with a high purity of 96.7%, as confirmed by X-ray diffraction (XRD) and X-ray fluorescence (XRF) analysis. Subsequent modification with Trimethylchlorosilane (TMCS) significantly enhanced the hydrophobicity of the silica, resulting in a contact angle of 99.84° with water. The synthesized silica-based material demonstrates promising potential as a self-cleaning surface coating, offering improved durability and ease of maintenance.